The compressive strength development and pH of cement mortars incorporating high volume supplementary cementitious materials under accelerated curing - Sumra Yousuf; Muhammad Rizwan; Belal Alsubari; Mustabshirha Gul; Muhammad Mahmood Ali; Muhammad Nasir Bashir; Abid Latif (Heliyon)
The durability and service life of concrete structures is primarily dependent on the performance of cement-based material (CBM). This performance of CBMs is linked to their pH directly. Literature suggests that when supplementary cementitious materials (SCMs) are used, the pH of CBMs decreases as a result Ca(OH)₂ consumption during the Pozzolanic reaction (PR). With the construction industry increasingly adopting blended cements for their technical, economic, and environmental benefits, the use of high volumes of SCMs remains a subject of caution. This study investigates the pH behavior of cement mortars modified by replacement of ordinary Portland cement (OPC) with three SCMs (50 %): fly ash (FA), ground granulated blast furnace slag (GGBS), and treated palm oil fuel ash (TPFA), both at early and later stages of curing. The pH values were measured at different curing ages, and thermal gravimetric analysis and X-ray diffraction were used to support the findings. Results indicated that the pH of mortars containing FA or GGBS showed only a slight decrease after 5 months compared to their initial pH values, remaining above 11.5, which is considered within the safe range for concrete durability. In contrast, the pH of TPFA blended mortars decreased significantly, dropping by approximately 14 %, indicating that TPFA had a more substantial impact on the alkalinity of the mortars. These findings suggest that the pH of CBMs is influenced by factors other than just the Ca(OH)₂ (Hydrated lime) content, such as the chemical composition and reactivity of the SCMs used, and that high volumes of TPFA may negatively affect long-term durability.